OA42 Evaluating the effects on a clinical service of introducing ultrasound for diagnosis of giant cell arteritis using Lean methodology. (23rd April 2022) - Rajeswaran, Thurkka; Barr, Andrew; Bassi, Vinod; Chakrabarty, Aruna; Cracknell, Alison; Darwood, Rosemary; Dass, Shouvik; Farrell, Shannon; Hunter, Jan; Mitchell, Thomas; Parvin, Jimmy; Sarker, Borsha; et al.
Abstract: Background/Aims: In our trust, patients with suspected giant cell arteritis (GCA) were promptly started on high-dose prednisolone. However, until 2019, patients were waiting on average 28.5 days (median) for confirmation of diagnostic decision, which was mostly due to the time taken for temporal artery biopsy (TAB) to be performed and reported. We have made two major changes to our pathway: firstly (Jan 2019) adding temporal artery ultrasound (TAUS), and secondly (Mar 2020), routing GP referrals through our Primary Care Access Line (PCAL) to an allocated rheumatology registrar based at the same site as the TAUS. We used Lean methodology to pre-specify metrics to evaluate our pathway. Aim and Purpose: To assess changes over time across our five prespecified domains: delivery, quality, service, morale and cost. Methods: We defined lead time as median time between entry to pathway and diagnostic confirmation. This was our delivery domain. We defined treatment for GCA as clinical diagnosis plus at least 6 months of treatment with "GCA-dose" steroids. Quality was measured for patients treated as GCA as the percentage with a positive confirmatory test; and for patients not treated as GCA as the cumulative prednisolone dose received for suspected GCA. Service and morale were assessed from patient and staff feedback, respectively. Cost was assessed via the patient-level costings team using standard NHS tariffs. We plotted a run chart by month and significant shift in delivery or quality was defined as six consecutive monthly values below the baseline median. Results: TAUS was performed a median of 2.5 days from referral. Agreement between TAB and TAUS results was good. The run chart showed a significant shift in our delivery. Lead time fell from 28.7 days to 19.2 days after introduction of ultrasound, and further down to 7.7 days after the utilisation of PCAL. A significant shift was also seen in quality metrics. Proportion of GCA with positive TAB/TAUS increased from 29% to 56.3% following the introduction of TAUS, and further to 75% on the utilisation of PCAL. The total mean prednisolone dose for patient without GCA fell from 1.335g to 0.439g after introducing TAUS, and down to 0.139g after introduction of PCAL. Within costs, average per-patient costs of TAB/TAUS declined from £1004/patient to £718/patient to £378/patient. However, total GCA pathway referrals increased from 6/month to 10/month to 24/month, increasing overall costs. Staff and patient feedback (service, morale) were overall positive, but revealed the need for further improvements to manage the additional complexity and volume. Conclusion: Lean methodology identified multiple metrics for evaluating the impact of TAUS and PCAL on our service. We have seen an improvement in delivery and quality. Measuring costs, morale and service helped identify unintended consequences and target further improvement. Disclosure: T. Rajeswaran: None. A. Barr: None. V. Bassi: None. A. Chakrabarty: None. A. Cracknell: None. R. Darwood: None. S. Dass: None. S. Farrell: None. J. Hunter: None. T. Mitchell: None. J. Parvin: None. B. Sarker: None. I. Simmons: None. K. Sinclair: None. K. Smith: None. A. Sweeting: None. R. Tue: None. M. Troxler: None. R. Wakefield: None. S.L. Mackie: Consultancies; consultancy for Roche, Sanofi, AstraZeneca, Abbvie on behalf of her institution. Other; support from Roche to attend EULAR2019.